Performance of Exotic Sweet Orange Genotypes at Dhankuta, Nepal - Pun, Amar Bahadur; Thakur, Manish Kumar (International Journal of Applied Sciences and Biotechnology, 2018)
The study was conducted to evaluate the varietal performance of sweet orange genotypes at National Citrus Research Program, Dhankuta, Nepal during 2015. Twenty 20 exotic as well as local genotypes planted in 2005 were evaluated for their fruit physio-chemical characteristics at their 10-years aged. Three genotypes: Malta Blood Red, Dhankuta Local and Valencia Late have resulted as superior genotypes for fruit yield characteristics. Some genotypes Delicious Seedless, Salustiana and Hamlin also exhibited excellent performance for their fruit size and weight; however these genotypes produced lower fruit number per plant. Pineapple, Meisheu-9, and Washington Navel had higher TSS. There was similar fruit maturity period commenced from 14 November to 28 December among the genotypes. Based on the results, the genotypes showing distinct characteristics of fruit yield and quality including fruit maturity period should be promoted to make variety diversity in Nepal. Int. J. Appl. Sci. Biotechnol. Vol 6(4): 308-312